FENOMENA HIJRAH KEKINIAN GENERASI Z DI KOTA KEDIRI DITINJAU DARI PERSPEKTIF TEORI PILIHAN RASIONAL - Tenika Illananingtyas; Ellyda Retpitasari (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2021)
In the era of modernization today, shaping society depends on social media. Not except for generation Z in their teens before adulthood, a period where this generation has a process searching for identity, including in the process of religion, the phenomenon of generation Z's present migration in Kediri viewed from the perspective of the Rational Choice Theory. In this study, researchers used qualitative research with a phenomenological approach by observing and interviewing the Z generation who following the present hijrah as many as 19 people, consisting of 6 men and 13 women. The result of research on the phenomenon of generation Z contemporary hijrah in Kediri City is behavioral and cultural changes without any influence of ideology as the examples of transnational ideology. It is popular that Generation Z has done since following the hijrah process follows the hijrah in the path of self-awareness. It changes the habitual attributes used in everyday life, such as how to wear clothes in stars. The hijrah carried out by Generation Z has nothing to do with things that lead to an interest in joining or choices in politics or political activities.